غلام احمد پرویز کے تصورِمرکزِملت کا تنقیدی جائزہ: A Critical review of Ghulam Ahmad Pervez's concept of "Makraz-e-Millat" - Ayub, Dr. Shahzada Imran; Muhammad Sohail Arif; Tauqir ul zaman (Al-Amīr Research Journal for Islamic Studies, 2023)
The Holy Quran is revealed by Allah Almighty to Prophet Muhammad ﷺ over approximately 23 years. Allah Almighty has given the command in the Quran Majeed for people to obey His Messenger. According to Ghulam Ahmad Parwez, the Quran Majeed states that obedience to Allah and His Messenger means obedience to the central authority of the Government named (Markaz e Millt). The Quran provides fundamental principles, such as prayer, fasting, pilgrimage, etc., but the detailed regulations are subject to the discretion of Markaz-e-Millat, who can adapt them according to the contemporary circumstances. Any changes made by the central authority in these regulations are considered legitimate and in accordance with the divine will. This study argues that the obedience to Allah and His Messenger mentioned in the Quran does not refer to obedience to the central authority of the Muslim community, known as "Markaz-e-Millat" (Center of the Community). Numerous Quranic verses warn against disobedience and denial of the Prophet. The Prophet's actions and behavior serve as a complete model for the community, and faith in him is a fundamental requirement of the religion. In conclusion, the idea that obedience to Allah and His Messenger essentially means obedience to the central authority of the Muslim community is an interpretation based on rational understanding but is ultimately unacceptable. Kyewords: Qu’rān, Interpretation, Ghulām Aḥmad Pervez Markaz-e-Millat, Government